2010
DOI: 10.1159/000314542
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Sodium and Potassium Transporters in the Course of Chronic Renal Failure

Abstract: Background: In chronic renal failure (CRF), residual nephrons can increase their excretion of sodium (Na) and potassium (K). However, the mechanisms of renal Na and K regulation in late-stage CRF have not been clearly investigated. Methods: We examined altered expression of major renal Na and K transporters in Sprague-Dawley rats at 4 and 12 weeks after a 5/6 nephrectomy. Results: CRF rats were azotemic and had gradually increased levels of urinary Na and K excretion over time. At 4 weeks, the abundance of Na-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 61 publications
(46 reference statements)
2
23
0
Order By: Relevance
“…Plasma and urine osmolality were measured with a cryoscopic osmometer (Osmomat 030-D-M; Gonotec, Berlin, Germany). The glomerular filtration rate (GFR) was calculated using the average of urea clearance and creatinine clearance (7). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Plasma and urine osmolality were measured with a cryoscopic osmometer (Osmomat 030-D-M; Gonotec, Berlin, Germany). The glomerular filtration rate (GFR) was calculated using the average of urea clearance and creatinine clearance (7). …”
Section: Methodsmentioning
confidence: 99%
“…Selected bands from these gels were scanned (GS-700 Imaging Densitometry; Bio-Rad) to determine the density (Molecular Analyst version 1.5; Bio-Rad), and relative amounts of protein were loaded into each lane. Finally, protein concentrations were corrected to reflect these measurements and were subjected to immunoblot analysis, using a previously described method (7). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data about CKD and expression of NKCC2 are limited. One study demonstrated an initial increase in NKCC2 expression after 5/6th nephrectomy in rats, later returning toward normal (85). Two studies in rats after uninephrectomy and salt loading demonstrated decreased expression of the NKCC2 (73,74).…”
Section: Does Kidney Disease Affect the Actions Of Furosemide?mentioning
confidence: 99%